Dissemination and Impact Amplified: How a Researcher–Reporter Collaboration Helped Improve the Criminal Justice Response to Victims With Untested Sexual Assault Kits - Lovell, Rachel E. (Journal of contemporary criminal justice, 2021)
We present a case study of a researcher–reporter collaboration that formed from an initiative to address thousands of previously untested rape kits in one Midwestern (U.S.) jurisdiction. We explore this symbiotic partnership by examining (a) how and why it formed; (b) the outcomes, including extensive and public dissemination and a unique project that surveyed 294 Ohio law enforcement agencies to see what happened after the rape kits were tested (Ohio Rape Kit Survey Project); and (c) the impact that the partnership, dissemination, and larger initiative had in sparking demonstrable change in how the justice system and the general public responded to and engaged with the issue of untested rape kits and with victims of sexual assault. We conclude with larger takeaways from this collaboration for researchers and reporters but also provide a framework for how this type of collaboration can be leveraged to produce change for the greater good.